Interferon gamma release assay, a powerful tool for the detection of human and bovine tuberculosis in the greater Cairo area compared to other diagnostic tools - A. Metwally, Mirihan; S. Yassin, Aymen; M. Riad, Emad; M. Hamouda, Hayam; A. Amin, Magdy (Penerbit Universiti Kebangsaan Malaysia, 2020)
Rapid detection is essential for the elimination and control of tuberculosis (TB) worldwide. Our study aimed to show the current and actual patterns of human and bovine TB distribution in the Greater Cairo Area community by the application of different TB diagnostic tools to individuals and farm animals with suspected TB. Both sputum and blood specimens were collected from 150 suspected human cases in the community. Sputum samples were examined using direct microscopy (Ziehl-Neelsen stain), culture on Lowenstein-Jensen medium, and real-time PCR. Blood samples were used for interferon gamma release assay (IGRA). In addition, lymph nodes and blood samples were collected from 57 tuberculin-positive animals. Lymph nodes were examined using direct microscopy (Ziehl-Neelsen stain), culture on Lowenstein-Jensen medium, and real-time PCR. Animal blood samples were also tested with IGRA. Sensitivity and specificity as well as positive and negative predictive values were calculated for all tests. The results showed that for both human and animal samples, IGRA provided the most accurate estimates of current TB infection compared to other tests. Furthermore, IGRA had the highest sensitivity and was the most convenient, proving its superiority compared to traditional methods in showing true levels of TB dissemination. This work shows that IGRA is a powerful tool for detection of TB in suspected humans and farm animals and should be incorporated into routine TB screening programs, which require more than one test.